Inferring putative virulence factors for Pythium insidiosum by proteomic approach - Chechi, Jéssica Luana [UNESP] (2019)
Pythium insidiosum is the etiologic agent of pythiosis, a life-threatening disease that affects human and animals, has difficult diagnosis, and therapy. Studies on protein characterization of P. insidiosum are scarce, so we aimed to determine the protein profile of P. insidiosum by mass spectrometry and bioinformatics strategies targeting in proteins that may act as putative virulence factors. Therefore, an extraction protocol was standardized to obtain the total proteins of P. insidiosum. By the analysis of Image Master 2D Platinum software, it was found that 186 spots ranging between 12 and 89 KDa and isoelectric point from 4 to 7. By the analysis of 2D-SDS-PAGE it was possible to visualize and excise 103 spots, which were hydrolyzed with trypsin and submitted to mass spectrometry, resulting in the identification of 36 different proteins. Three of them were classified as proteins supposedly related to virulence factors due to its functions, such as glucan 1,3-beta glucosidase, Heat shock protein (Hsp) 70 and enolase. These results may contribute to a better understanding of the virulence factors of this medically important oomycete, as well as to subsidize new studies on diagnosis and therapeutic approaches.